2007
DOI: 10.1038/sj.mt.6300016
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated Virus Type 5 Reduces Learning Deficits and Restores Glutamate Receptor Subunit Levels in MPS VII Mice CNS

Abstract: A major challenge in treating lysosomal storage diseases with enzyme therapy is correcting symptoms in the central nervous system (CNS). This study used a murine model of mucopolysaccharidosis type VII (MPS VII) to test whether pathological and functional CNS defects could be corrected by expressing beta-glucuronidase via bilateral intrastriatal injection of adeno-associated virus type 5 (AAV5betagluc) vectors. After injecting AAV5betagluc, different brain regions expressed active beta-glucuronidase, which cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 38 publications
0
21
1
Order By: Relevance
“…This is consistent with the findings of Lubansu et al where AAV serotype 5 was shown to be ineffective in transducing rat embryonic (E15) ganglionic eminence cultures. These data are in contrast to studies showing that AAV serotype 5 was efficient at transducing cells in adult mouse 31,32 and non-human primate brain. 33,34 This discrepancy suggests that the availability of AAV5-binding sites, such as 2,3-linked sialic acid, 35 and potential receptors may vary from gestation through to adulthood.…”
Section: Discussioncontrasting
confidence: 99%
“…This is consistent with the findings of Lubansu et al where AAV serotype 5 was shown to be ineffective in transducing rat embryonic (E15) ganglionic eminence cultures. These data are in contrast to studies showing that AAV serotype 5 was efficient at transducing cells in adult mouse 31,32 and non-human primate brain. 33,34 This discrepancy suggests that the availability of AAV5-binding sites, such as 2,3-linked sialic acid, 35 and potential receptors may vary from gestation through to adulthood.…”
Section: Discussioncontrasting
confidence: 99%
“…These are limited as therapeutic agents cannot cross the BBB. Thus, the clinical severity including neuropsychiatric symptoms and the lack of efficient therapy led to trials of gene therapy (ex vivo and in vivo) and development of stem cell and encapsulation cell therapeutic approaches for disease [59][60][61][62]. Injections of recombinant virus vectors for systemic and CNS malfunctions directly into the brain have bypassed the BBB but the possibilities for tumor formation and toxicity could limit their development and use.…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%
“…Recombinant AAVs are being investigated as vectors for clinical gene transfer to a wide variety of cells and tissues (Hasbrouck and High, 2008; Kota et al, 2009; Maguire et al, 2009; Maguire et al, 2010; Muzyczka, 1992; Srivastava, 2008; Wagner et al, 1999). Transduction with AAV vectors has been shown to result in long-term transgene expression in vivo in several cell types including skeletal muscle, photoreceptors, liver, and neuronal cells (Daya and Berns, 2008; Hasbrouck and High, 2008; Liu et al, 2007). As a result, AAV was used in the first regulatory approval of a gene therapy product in Western nations, in 2012 within the European Union.…”
Section: Introductionmentioning
confidence: 99%